Bacteria in an intense competition for iron: Key component of the Campylobacter jejuni iron uptake system scavenges enterobactin hydrolysis product - Raines, Daniel J. (Proc Natl Acad Sci U S A, 2016)
To acquire essential Fe(III), bacteria produce and secrete siderophores with high affinity and selectivity for Fe(III) to mediate its uptake into the cell. Here, we show that the periplasmic binding protein CeuE of Campylobacter jejuni, which was previously thought to bind the Fe(III) complex of the hexadentate siderophore enterobactin (K(d) ∼ 0.4 ± 0.1 µM), preferentially binds the Fe(III) complex of the tetradentate enterobactin hydrolysis product bis(2,3-dihydroxybenzoyl-l-Ser) (H(5)-bisDHBS) (K(d) = 10.1 ± 3.8 nM). The protein selects Λ-configured [Fe(bisDHBS)](2−) from a pool of diastereomeric Fe(III)-bisDHBS species that includes complexes with metal-to-ligand ratios of 1:1 and 2:3. Cocrystal structures show that, in addition to electrostatic interactions and hydrogen bonding, [Fe(bisDHBS)](2−) binds through coordination of His227 and Tyr288 to the iron center. Similar binding is observed for the Fe(III) complex of the bidentate hydrolysis product 2,3-dihydroxybenzoyl-l-Ser, [Fe(monoDHBS)(2)](3−). The mutation of His227 and Tyr288 to noncoordinating residues (H227L/Y288F) resulted in a substantial loss of affinity for [Fe(bisDHBS)](2−) (K(d) ∼ 0.5 ± 0.2 µM). These results suggest a previously unidentified role for CeuE within the Fe(III) uptake system of C. jejuni, provide a molecular-level understanding of the underlying binding pocket adaptations, and rationalize reports on the use of enterobactin hydrolysis products by C. jejuni, Vibrio cholerae, and other bacteria with homologous periplasmic binding proteins.